Metalloproteomic approach to liver tissue of rats exposed to mercury - Santiago, Maria Gabriela A. [UNESP]; Faria, Victor Diego [UNESP]; Cirinêu, Felipe Dalmazzo [UNESP]; Queiroz da Silva, Lucas Luan de Lima [UNESP]; de Almeida, Emerson Carlos [UNESP]; Cavallini, Nubya Gonçalves [UNESP]; Souza Vieira, José Cavalcante [UNESP]; Henrique Fernandes, Ana Angélica [UNESP]; Braga, Camila Pereira; Zara, Luís Fabrício; Rabelo Buzalaf, Marília Afonso; Adamec, Jiri; et al. (Elsevier, 2023)
The aims of this study were to identify mercury-associated protein spots in the liver tissue of rats exposed to low concentrations of mercury and to elucidate the physiological and functional aspects of the proteins identified in the protein spots. Therefore, proteomic analysis of the liver tissue of Wistar rats exposed to mercury chloride (4.60 μg kg−1 in Hg2+) was performed for thirty days (Hg-30 group) and sixty days (Hg-60 group). The proteomic profile of the liver tissue of the rats was obtained by two-dimensional electrophoresis (2D-PAGE), and the determinations of total mercury in the liver tissue, pellets and protein spots were performed by graphite furnace atomic absorption spectrometry (GFAAS). ImageMaster 2D Platinum 7.0 software was used to identify the differentially expressed mercury-associated protein spots, which were then characterized by liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). The determinations by GFAAS indicated a total mercury bioaccumulation of 2812% in the Hg-30 group and 3298% in the Hg-60 group and 10 mercury-associated protein spots with a concentration range of 51 ± 1.0 to 412 ± 6.00 mg kg−1 in the 2D PAGE gels from the liver tissue of the Hg-60 group. The LC–MS/MS analyses allowed the identification of 11 metal binding proteins in mercury-associated protein spots that presented fold change with upregulation >1.5, downregulation < −1.7 or that were expressed only in the Hg-60 group. Using the FASTA sequences of the proteins identified in the mercury-associated protein spots, bioinformatics analyses were performed to elucidate the physiological and functional aspects of the metal binding proteins, allowing us to infer that enzymes such as GSTM2 presented greater mercury concentrations and downregulation < −3; Acaa2 and Bhmt, which showed expression only in the Hg-60 group, among others, may act as potential mercury exposure biomarkers.
Keywords: Mercury bioaccumulation; Mercury exposure biomarkers; Mercury species; Metal binding proteins